2013
DOI: 10.5114/aoms.2013.36911
|View full text |Cite
|
Sign up to set email alerts
|

Nonvariceal upper gastrointestinal tract bleeding – risk factors and the value of emergency endoscopy

Abstract: IntroductionUpper gastrointestinal tract bleeding (UGIB) remains a valid issue of modern medicine. The mortality and recurrence rates remain high and have not decreased as expected over the past decades. Aim of the study: to assess the treatment outcomes of nonvariceal UGIB depending on the timing of endoscopy (urgent vs. elective) and to perform an analysis of risk factors for death in patients with nonvariceal UGIB.Material and methodsComparative evaluation of treatment outcomes in two groups of patients. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Based on the results of this previous study, we propose that the updated CCI may also be useful for predicting prognosis in upper gastrointestinal mucosal disorder patients. In fact, Wierachowski et al reported that CCI was significantly higher in the death group compared to the survival group in case of gastrointestinal bleeding [16]. Therefore, we compared various risk scores, including the original CCI and the updated CCI in gastrointestinal mucosal disorder patients, to predict their prognosis.…”
Section: Score Development Process and Research Resultsmentioning
confidence: 99%
“…Based on the results of this previous study, we propose that the updated CCI may also be useful for predicting prognosis in upper gastrointestinal mucosal disorder patients. In fact, Wierachowski et al reported that CCI was significantly higher in the death group compared to the survival group in case of gastrointestinal bleeding [16]. Therefore, we compared various risk scores, including the original CCI and the updated CCI in gastrointestinal mucosal disorder patients, to predict their prognosis.…”
Section: Score Development Process and Research Resultsmentioning
confidence: 99%
“…Likewise, subsequent studies have confirmed that it can evaluate the risk of bleeding within 30 days after discharge, or even within 1 year, and the study population has been extended to all patients receiving dual antiplatelet therapy after PCI [21]. Systolic blood pressure [22], plasma albumin [13,22], hematocrit [12,23]and ALT [14]included in the model were applied as predictors of death because of GIB by other risk score, so the model may also has a certain ability to predict the mortality of GIB.…”
Section: Discussionmentioning
confidence: 99%
“…An association between comorbidity as measured by the Charlson index and major bleeding has been previously described in patients undergoing percutaneous coronary intervention, 36 as well in other clinical settings. 37,38 Some of the components of the Charlson score are well-established predictors for bleeding (neoplasms, renal failure, stroke, hepatic disease). In addition, an important interrelation between frailty, comorbidity and other agingrelated variables has been consistently described.…”
Section: Discussionmentioning
confidence: 99%
“…• The functional capacity for basic activities of daily living was assessed by the Barthel index. 14 This is an ordinal scale with a total score of 0 to 100, where the intermediate ranges help evaluate the different degrees of dependency: total (0-20), severe (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), moderate (41-60), light (61-90) and independent (> 90). Instrumental activities were evaluated with the Lawton-Brody index.…”
Section: Baseline Geriatric Assessmentmentioning
confidence: 99%